No, 12x and 14y are not like terms. Like terms are terms that have the same variable raised to the same power. In this case, 12x has a variable x raised to the first power, while 14y has a variable y raised to the first power. Since the variables are different, they are not considered like terms.
12x+14
12x + 17 - (9x - 2)Eliminate parentheses:12x + 17 - 9x + 2Combine the 'x' terms:3x +17 + 2Combine the numerical terms:3x + 19
4x2 is 8+ 12x + 3 collect like terms, 8+3= 11, 12x+11 to solve for x, transpose the 11 to the other side of the = sign, 12x=-11, divide by 12, x=-11/12
5y - 14y = -9y
I think I remember it meaning when two or more terms(parts of the equation) are similar like 7 + 3x = 12x - 5. 5 & 7 are like terms. So maybe likely is it as a verb or something like that? Idk. At least I tried.
It cannot be determined without knowing the values of xand y
You mean like these?: 9 * 2 - (-2 + 9) + 15 / (4.5 + 3) (6x + 7y) * 2 (y - 6x)=(6x*2y)-(6x*12x)+(2y*7y)-(12x*7y)=12xy-72x^2+14y^2-84xy=14y^2-72x^2-72xy
After collecting like terms, (3 - 5x - 5 - 12x) reduces to (-2 - 17x).
Yes, 12x and 5x are like terms because they have the same variable, which is 'x'. Like terms are terms that have the same variable(s) raised to the same power(s). In this case, both terms have 'x' raised to the power of 1. Therefore, they can be combined or simplified together in algebraic expressions.
12x+14
12x+15p-6p+11x = 12x+11x+15p-6p = (12+11)x+(15-6)p = 23x + 9p
Thee of them which are 14x, -x and 2x = 15x
12x + 17 - (9x - 2)Eliminate parentheses:12x + 17 - 9x + 2Combine the 'x' terms:3x +17 + 2Combine the numerical terms:3x + 19
4x2 is 8+ 12x + 3 collect like terms, 8+3= 11, 12x+11 to solve for x, transpose the 11 to the other side of the = sign, 12x=-11, divide by 12, x=-11/12
Terms with the same variable(s). In like terms, you may add, subtract, multiply, or divide them. In the equation 3x - 5ax + 9x = 7ax, the 5x and the 10x are like terms because they both contain variables of the same value. Thus, we are allowed to add them up and get 12x. The -5ax and the 7ax are also like terms and if we add 5ax to both sides (after we add 3x to 9x), we'll get the equation 12x = 12ax.
6x2 - 12x [take out what both terms have in common] 6x(x - 2) [if you multiply 6x by both terms in the parenthesis you will get your original answer]
5y - 14y = -9y